An Overview of 3-D Printing in the Manufacturing, Aerospace, and Automotive Industries - Lim, Choon Wee Joel (2018)
Additive manufacturing (AM), also known as threedimensional (3-D) printing, is the process of joining materials to make objects from 3-D model data, usually layer upon layer. Contrary to conventional manufacturing techniques, parts are built up by the addition of materials one layer at a time, corresponding to the cross section of the sliced 3-D model. Due to the nature of AM's layer-wise fabrication process, the need for fixtures and cutting tools are eliminated. Furthermore, computer-aided design (CAD) tools have allowed design optimization on demand, enabling the production of customizable parts readily.